Multivariate decomposition of shift toward public facilities for inpatient care in rural India: evidence from National Sample Survey - Sharma, Sandeep; Kumar, E Lokesh; Kotwal, Atul (Frontiers in Public Health, 2025)
IntroductionPublic facilities in health systems are essential for improving access and ensuring equity. Public facility utilization for inpatient care in rural areas increased between the most recent National Sample Survey (NSS) health rounds of 2014 and 2017–2018. This study conducted a decomposition analysis to identify the underlying causes that contributed to this increase in public facility utilization.Materials and methodsThe study used the latest available unit-level data from the 2014 and 2017–2018 NSS Health Survey. The study employed multivariate decomposition analysis based on the existing behavioral model of access to health facilities.ResultsThe public facility utilization for inpatient care in rural areas increased from 41.6% to 45.3% between 2014 and 2017–2018. The results of the multivariate decomposition analysis indicate that differences in coefficients account for 81% of the increase in the utilization of public health facilities. Within the coefficients, this increase is mainly driven by the increase in the utilization of public facilities among those residing in states with relatively better public health systems (54.3%) and among the richest consumption class (45.4%).Discussion and conclusionThe utilization of public facilities for inpatient care increased between 2014 and 2017–2018 in rural India. This increase in utilization, though, was mostly driven by increased utilization among people residing in states with relatively better public health systems and by those belonging to the richer consumption classes. The study indicates that improved public health systems can play an important role in increasing footfall in public health facilities.